Exploring the effect of a microencapsulated citrus essential oil on in vitro fermentation kinetics of pig gut microbiota - Ambrosio, Carmen M. S.; Alvim, Izabella D.; Wen, Caifang; Gómez Expósito, Ruth; Aalvink, Steven; Contreras Castillo, Carmen J.; Da Gloria, Eduardo M.; Smidt, Hauke (Frontiers in Microbiology, 2022)
Essential oils (EOs) have emerged as a potential alternative to antibiotics in pig breeding due to their antimicrobial properties. Citrus EOs, a common by-product of the orange juice industry, can be an interesting alternative from a financial perspective due to their huge offer in the global market. Thus, the effect of a citrus EO, and specifically different formulations of Brazilian Orange Terpenes (BOT), on pig gut microbiota was evaluated by means of an in vitro fermentation model simulating different sections of the pig gut (stomach, ileum, and colon). Treatments consisted in: BOT in its unprotected form (BOT, 1.85 and 3.70 mg/mL), microencapsulated BOT (MBOT, 3.50 and 7.00 mg/mL), colistin (2 μg/mL), and a control. BOT and MBOT altered in a similar way the total bacterial 16S rRNA gene copies in the stomach only from 18 h of incubation onwards, and no metabolite production in terms of short-chain fatty acids (SCFAs) was detected. In ileal and colonic fermentations, BOT and MBOT affected ileal and colonic microbiota in terms of total bacterial 16S rRNA gene copies, reduced phylogenetic diversity, and altered composition (p < 0.05) as evidenced by the significant reduction of certain bacterial taxa. However, more pronounced effects were found for MBOT, indicating its higher antimicrobial effects compared to the unprotected BOT, and suggesting that the antibacterial efficiency of the unprotected BOT was probably enhanced by microencapsulation. Furthermore, MBOT stimulated lactate production in ileal fermentations and greatly stimulated overall SCFA production in colonic fermentations. This indicates that besides the shifts in ileal and colonic microbiota by the delivered EO (BOT), the wall material of microcapsules (chitosan/modified starch) might have worked as an additional carbon source with prebiotic functioning, stimulating growth and metabolic activity (SCFAs) of colonic bacteria.